Penanaman Pohon Kelompok 1 Desa Wanaraja “Dia Yang Menanam Pohon, Menaruh Harapan” - Mubarok, Muhammad Syauqi; Syahril, Hilman; Tizani, Sofyan; Abdurrohim, Dede; Nurhidayat, Nurhidayat; Pratama, Reifalga Gais; Fauzi, Rizki; Novianti, Lulu Putri; Saroh, Laela; Islami, Wulan; Rohman, Taupik Saepul; Paris, Muhammad Diki; Juanda, Risdi; Misela, Dela; Assyifa, Nur; Huda, Latipah Munawaroh; Hidayatulloh, Ginda; Ismail, Saep; Ramdan, Muhammad; Indriyani, Sagita Aulia; Pratama, Adhitya Surya (Institut Teknologi Garut, 2022)
The lack of greenery and the large amount of vacant land in Wanaraja Village has caused a lot of problems faced by the local community, one of the problems faced is the problem of flooding. According to data released from the Wanaraja Village government that floods often occur in the rainy season from Sukamenak Village to Wanaraja Village RW.08 which of course these floods will greatly disrupt the lives of the surrounding community both in terms of damage to houses and the contents of goods or other public infrastructure . This tree planting work program aims to help withstand water pressure due to heavy rains besides that this work program can prevent soil erosion so as to prevent floods or landslides. The results achieved are that the environment of Wanaraja Village will become more well-maintained. Besides that, it is hoped that tree planting can prevent disasters such as floods or landslides that have occurred before.